Risk analysis and risk mitigation approaches: waterborne pathogens that become foodborne pathogens through irrigation - Allende, A.; Drechsel, Pay (2023)
Ensuring the microbial safety of irrigation water is vital to preventing the contamination of fresh produce with waterborne pathogens. This section addresses how agricultural water, particularly when sourced from polluted or untreated wastewater, poses significant health risks by transmitting bacteria, viruses, and parasites to humans through direct contact or consumption. It emphasizes a fit-for-purpose approach to water use, advocating for microbial risk assessments tailored to crop types, water delivery systems, and local conditions. Multiple barrier strategies such as improved irrigation methods, crop restrictions, and hygienic post-harvest practices are outlined as core components of risk mitigation. Decision trees (DTs) and risk-based guidelines, including those from WHO, Codex Alimentarius, and ISO, are presented as tools to support farmer decision-making and policy implementation. The chapter further highlights practical measures like hand hygiene, use of protective clothing, and on-farm water treatment. While quantitative microbial risk assessments (QMRAs) offer scientific precision, the lack of access in many regions necessitates adaptable, low-cost solutions. The importance of awareness-building and behavior change is underscored, with a call for further research into the effectiveness and adoption of water safety interventions.